Negative pole piece, secondary battery and electronic device
By setting a first material layer to relieve the expansion stress of silicon material in the negative electrode sheet of the lithium-ion battery, the purple spot problem at the beginning and end of the negative electrode sheet is solved, the energy density and dynamic performance of the battery are improved, and safety risks are reduced.
Patent Information
- Application Number
- CN202510390637.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-22
AI Technical Summary
During the cycle, the negative electrode sheet of lithium-ion battery has purple spots on the head and tail due to the change in the volume of silicon-containing material, which affects the dynamic performance and safety of the battery.
A first material layer containing a smaller volume change rate is arranged between the negative electrode current collector and the second material layer containing silicon elements, to regulate the volume change rate, thickness and mass percentage content of the first material layer, to alleviate the influence of the alternating expansion stress of the silicon material particles on the current collector, and to improve the ductility and bonding state of the current collector.
It reduces the probability of deformation and bond failure of the negative electrode sheet, improves the energy density and dynamic performance of the battery, and reduces the risk of liquid leakage.
Smart Images

Figure CN120356893A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technologies, and particularly to a negative electrode sheet, a secondary battery, and an electronic device. Background Art
[0002] With the popularization and replacement of consumer electronic products such as smart phones, laptop computers, and smart homes, the market demand for consumer lithium-ion batteries has been continuously growing. Due to the diversified development of electronic products, the requirements for lithium-ion batteries are also getting higher and higher, and lithium-ion batteries have also achieved great development.
[0003] As a material for the negative electrode of a lithium-ion battery, silicon material has a higher energy density and a higher theoretical specific capacity compared to the traditional graphite negative electrode. However, the silicon-containing material has a large volume change during the cycling process. The negative electrode current collector is affected by the alternating expansion stress of the silicon-containing material particles, and it is prone to extension in the length direction and the width direction, resulting in purple spots appearing at the head and tail of the negative electrode sheet. Summary of the Invention
[0004] The purpose of the present application is to provide a negative electrode sheet, a secondary battery, and an electronic device to alleviate the purple spot phenomenon at the head and tail of the negative electrode sheet.
[0005] It should be noted that in the summary of the invention of the present application, the lithium-ion battery is taken as an example of the secondary battery to explain the present application, but the secondary battery of the present application is not limited to the lithium-ion battery. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a first material layer and a second material layer, and the first material layer is provided between the negative electrode current collector and the second material layer; the total thickness of the negative electrode active material layer is T1 μm, the thickness of the first material layer is T2 μm, 5 ≤ T2 ≤ 8, 4.6% ≤ T2 / T1×100% ≤ 8.0%; the first material layer includes a first active material, and the volume change rate of the first active material ≤ 10%, and the volume change rate is the volume change rate of the first active material before and after lithium intercalation; the second material layer includes a second active material, and the second active material includes silicon element. Both T1 and T2 are the thicknesses on one side of the current collector. For the negative electrode plate provided by the first aspect of the present application, by providing a first material layer containing a first active material with a small volume change rate between the negative electrode current collector and the second material layer containing silicon element, and regulating the volume change rate of the first active material, the single-layer thickness of the first material layer, and the ratio of the single-layer thickness of the first material layer to the total thickness of the negative electrode active material layer within the scope of the present application, the lithium intercalation expansion of the first active material during the charge and discharge process of the secondary battery is small, the expansion stress of the first material layer can be reduced, and the influence of the alternating expansion stress of the second active material particles containing silicon on the extension of the negative electrode current collector in the length direction and width direction (hereinafter referred to as XY extension) can be better improved. The tensile stress on the negative electrode current collector in its length direction and width direction is reduced, and the XY extension of the negative electrode current collector is improved. In this way, the possibility of the negative electrode plate deforming and wrinkling is reduced, so that the bonding state between the negative electrode plate and the separator can be improved, and the probability of purple spot phenomenon caused by the blockage of the lithium ion path due to the loss of bonding between the negative electrode plate and the separator and insufficient lithium intercalation at the interface can be reduced. In addition, the cooperation of the first material layer and the second material layer can also reduce the energy density loss brought by the first active material, and the capacity of the second active material can be fully exerted, so that the negative electrode active material layer has a high capacity. Therefore, the purple spot phenomenon at the head and tail of the negative electrode plate can be alleviated, so that the secondary battery has a high energy density on the basis of improved kinetic performance. It can also alleviate the safety problem that the XY extension of the negative electrode current collector pierces the outer package and causes liquid leakage.
[0007] In some embodiments of the present application, based on the mass of the negative electrode active material layer, the mass percentage content of the first active material is W1, 6.5% ≤ W1 ≤ 8.5%. Regulating the mass percentage content of the first active material within the above range is beneficial to alleviating the influence of the alternating expansion stress brought by the silicon material particles on the negative electrode current collector to improve the XY extension of the negative electrode current collector. It is also beneficial to the improvement of the energy density of the secondary battery.
[0008] In some embodiments of the present application, based on the mass of the negative electrode active material layer, the mass percentage content of silicon element is W2, and 0.4 ≤ W2 / W1 ≤ 4.6. By controlling the value of the ratio W2 / W1 of the mass percentage content of silicon element in the negative electrode active material layer to the mass percentage content of the first active material within the above range, the purple spot phenomenon at the head and tail of the negative electrode pole piece can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, a higher energy density can be achieved.
[0009] In some embodiments of the present application, 1.4 ≤ W2 / W1 ≤ 3.6. By controlling the value of the ratio W2 / W1 of the mass percentage content of silicon element in the negative electrode active material layer to the mass percentage content of the first active material within the above range, it is beneficial to better relieve the expansion stress brought by the silicon element, and it is beneficial to further alleviate the purple spot phenomenon at the head and tail of the negative electrode pole piece, and on the basis of improving the kinetic performance of the secondary battery, a higher energy density can be achieved.
[0010] In some embodiments of the present application, the types of the first active material include at least one of lithium titanate, titanium dioxide, carbon nanotubes or graphene. Selecting the above types of the first active material for the first material layer can relieve the alternating expansion stress brought by the second active material containing silicon element, reduce the tensile stress on the negative electrode current collector in its length direction and width direction, and improve the XY extension of the negative electrode current collector. The purple spot phenomenon at the head and tail of the negative electrode pole piece can be alleviated.
[0011] In some embodiments of the present application, the types of the second active material include at least one of silicon carbide compounds, silicon oxide compounds or pure silicon. The above types of the second active material can provide a higher capacity for the negative electrode pole piece, so that the secondary battery has a higher capacity and energy density.
[0012] In some embodiments of the present application, the particle sizes of lithium titanate and titanium dioxide independently satisfy: 1.1 μm ≤ Dv90 ≤ 1.5 μm, 0.7 μm ≤ Dv50 ≤ 1.0 μm; the length of the carbon nanotubes is from 0.1 μm to 1.0 μm; the sheet diameter of the graphene is from 0.5 μm to 1.0 μm. By controlling the particle sizes of lithium titanate and titanium dioxide, the length of the carbon nanotubes and the sheet diameter of the graphene within the above range, lithium titanate, titanium dioxide, carbon nanotubes and graphene all have higher ionic conductivity and more active sites. Using them as the first active material in the first material layer is beneficial to further relieve the alternating expansion stress brought by the second active material containing silicon material, so as to further improve the XY extension of the negative electrode current collector, and is also beneficial to reducing the loss of the first active material to the energy density. The purple spot phenomenon at the head and tail of the negative electrode pole piece can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, a higher energy density can be achieved.
[0013] In some embodiments of the present application, the lithium intercalation potential of the first active material is U, where 0.13 V ≤ U ≤ 1.60 V. By regulating the lithium intercalation potential of the first active material within the above range, during the charge and discharge process of the secondary battery, it is beneficial for the first active material to preferentially undergo small lithium intercalation expansion, so as to relieve the large lithium intercalation expansion brought by the silicon-containing second active material, thereby reducing the tensile stress on the negative electrode current collector in the length and width directions caused by the alternating expansion stress of the second active material particles, and improving the XY extension of the negative electrode current collector. The purple spot phenomenon at the head and tail of the negative electrode pole can be alleviated.
[0014] In some embodiments of the present application, the specific surface areas of lithium titanate and titanium dioxide are each independently B1, where 3.1 m 2 / g ≤ B1 ≤ 8.2 m 2 / g; the specific surface areas of graphene and carbon nanotubes are each independently B2, where 15 m 2 / g ≤ B2 ≤ 220 m 2 / g. By regulating the specific surface areas of lithium titanate, titanium dioxide, carbon nanotubes and graphene within the above range, it is beneficial for the first active material to have more active sites during the reaction process, the purple spot phenomenon at the head and tail of the negative electrode pole can be alleviated, and the first active material will also provide a little capacity, which is beneficial to improving the volume energy density of the secondary battery. It can also alleviate the safety problem of leakage caused by the XY extension of the negative electrode current collector piercing the outer package.
[0015] In some embodiments of the present application, the powder conductivity of lithium titanate is α1, where 2 × 10 -6 S / m ≤ α1 ≤ 1 × 10 - 4 S / m; the powder conductivity of titanium dioxide is α2, where 3 × 10 -14 S / m ≤ α2 ≤ 3 × 10 -10 S / m; the powder conductivity of graphene is α3, where 3 × 10 6 S / m ≤ α3 ≤ 1 × 10 8 S / m; the powder conductivity of carbon nanotubes is α4, where 3 × 10 6 S / m ≤ α4 ≤ 1 × 10 8 S / m.
[0016] In some embodiments of the present application, the powder lithium ion diffusion coefficient of lithium titanate and titanium dioxide is δ1, where 1.25 × 10 -9 cm 2 / s ≤ δ1 ≤ 3 × 10 -7 cm 2 / s; the powder lithium ion diffusion coefficient of graphene and carbon nanotubes is δ2, where 1 × 10 -7 cm 2 / s ≤ δ2 ≤ 1 × 10 -4 cm2 / s. The powder lithium-ion diffusion coefficient δ of the first active material is within the above range, and lithium ions have a good diffusion rate in the secondary battery.
[0017] In some embodiments of the present application, the initial Coulombic efficiency of the first active material is E, 60% < E ≤ 85%. This indicates that the first active material has a relatively high initial Coulombic efficiency.
[0018] In some embodiments of the present application, the adhesion force between the first material layer and the negative electrode current collector is N1, 26.5 N / m ≤ N1 ≤ 55 N / m. This indicates that there is a relatively high adhesion force between the first material layer and the negative electrode current collector.
[0019] In some embodiments of the present application, the negative electrode current collector includes any one of a copper current collector, a foam copper current collector, a nickel current collector, or a stainless steel current collector. When the negative electrode current collector of the above types is applied to the negative electrode plate, the XY extension of the negative electrode current collector can be improved, and the probability of purple spots appearing at the head and tail of the negative electrode plate and leakage caused by piercing the outer package is reduced.
[0020] In some embodiments of the present application, the peel force between the first material layer and the second material layer is N2, 16.7 N / m ≤ N2 ≤ 46.2 N / m. This indicates that there is a relatively high peel force between the first material layer and the second material layer.
[0021] In some embodiments of the present application, the resistivity of the negative electrode plate in the thickness direction is Z, 3.7 Ω·cm ≤ Z ≤ 15.2 Ω·cm. When the resistivity Z of the negative electrode plate in the thickness direction is within the above range, it is beneficial to the transport of lithium ions in the negative electrode plate.
[0022] The second aspect of the present application provides a secondary battery, which includes the negative electrode plate described in any of the foregoing embodiments. Therefore, the secondary battery has good kinetic performance and a relatively high energy density.
[0023] The third aspect of the present application provides an electronic device, which includes the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device has good performance in use.
[0024] Advantages of the present application:
[0025] The present application provides a negative electrode plate, a secondary battery, and an electronic device. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a first material layer and a second material layer, and the first material layer is disposed between the negative electrode current collector and the second material layer. The total thickness of the negative electrode active material layer is T1 μm, the thickness of the first material layer is T2 μm, 5 ≤ T2 ≤ 8, and 4.6% ≤ T2 / T1×100% ≤ 8.0%. The first material layer includes a first active material, and the volume change rate of the first active material ≤ 10%, and the volume change rate is the volume change rate of the first active material before and after lithium intercalation. The second material layer includes a second active material, and the second active material includes silicon element. By disposing the first material layer containing the first active material with a small volume change rate between the negative electrode current collector and the second material layer containing silicon element, and regulating the volume change rate of the first active material, the single-layer thickness of the first material layer, and the ratio of the single-layer thickness of the first material layer to the total thickness of the negative electrode active material layer within the scope of this application, the lithium intercalation expansion of the first active material during the charge and discharge process of the secondary battery is small, the expansion stress of the first material layer can be reduced, and the influence of the alternating expansion stress of the second active material particles containing silicon on the XY extension of the negative electrode current collector can be better improved. The tensile stress received by the negative electrode current collector in its length direction and width direction is reduced, and the XY extension of the negative electrode current collector is improved. In this way, the possibility of the negative electrode plate deforming and wrinkling is reduced, thereby improving the bonding state between the negative electrode plate and the separator, and reducing the probability of purple spot phenomenon caused by the blockage of the lithium ion path due to the loss of bonding between the negative electrode plate and the separator, resulting in insufficient lithium intercalation at the interface. In addition, the cooperation of the first material layer and the second material layer can also reduce the energy density loss brought by the first active material, and the capacity of the second active material can be fully exerted, so that the negative electrode active material layer has a high capacity. Therefore, the purple spot phenomenon at the head and tail of the negative electrode plate can be alleviated, so that the secondary battery has a high energy density on the basis of improved kinetic performance. It can also alleviate the safety problem of the negative electrode current collector piercing the outer package and causing liquid leakage due to XY extension. The secondary battery using the negative electrode plate of the present application has good kinetic performance, and the electronic device has good use performance.
[0026] Of course, implementing any product or method of the present application does not necessarily require achieving all the above-mentioned advantages simultaneously. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present application. For those of ordinary skill in the art, other embodiments can also be obtained according to these drawings.
[0028] Figure 1 Schematic cross-sectional structure diagram of the negative electrode sheet along its own thickness direction and length direction for some embodiments of the present application.
[0029] Reference numerals: 100 - negative electrode sheet; 10 - negative electrode current collector; 11 - first material layer; 12 - second material layer; 20 - negative electrode active material layer. Detailed implementation manners
[0030] Next, the technical solutions in the present application will be clearly and completely described in conjunction with the embodiments of the present application and the drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0031] It should be noted that in the specific implementation manners of the present application, a lithium-ion battery is taken as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to lithium-ion batteries.
[0032] In a first aspect of the present application, a negative electrode sheet is provided. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a first material layer and a second material layer, and the first material layer is disposed between the negative electrode current collector and the second material layer. The total thickness of the negative electrode active material layer is T1 μm, the thickness of the first material layer is T2 μm, 5 ≤ T2 ≤ 8, 4.6% ≤ T2 / T1 × 100% ≤ 8.0%. The first material layer includes a first active material, and the volume change rate of the first active material before and after lithium intercalation ≤ 10%, and the volume change rate is the volume change rate of the first active material before and after lithium intercalation. Preferably, the volume change rate of the first active material is 0.2% to 10%. More preferably, the volume change rate of the first active material is 0.2% to 8.5%. The second material layer includes a second active material, and the second active material includes silicon element.
[0033] For the convenience of understanding, in the present application, the own length direction of the negative electrode sheet is defined as X, and the own thickness direction is defined as Z. It should be understood that the above definitions of directions are for the purpose of conveniently describing the present application, and the directions defined in the present application can be understood according to the relative positions of the drawings and the actual product elements. Moreover, the own length direction and thickness direction of the negative electrode current collector, the first material layer, and the second material layer are the same as those of the negative electrode sheet. The above "negative electrode active material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode active material layer is disposed on one surface or two surfaces of the negative electrode current collector, and the above "surface" can be a partial surface or the entire surface of the negative electrode current collector. For example Figure 1As shown, the negative electrode plate 100 includes a negative electrode current collector 10 and a negative electrode active material layer 20. The negative electrode active material layer 20 is disposed on two surfaces of the negative electrode current collector 10. The negative electrode active material layer 20 includes a first material layer 11 and a second material layer 12. The first material layer 11 is disposed between the negative electrode current collector 10 and the second material layer 12. The single-layer thickness of the first material layer 11 is shown as T2, and the single-layer thickness of the second material layer 12 is shown as T3. The total thickness of the negative electrode active material layer 20 is the sum of the single-layer thickness of the first material layer 11 and the single-layer thickness of the second material layer 12. The total thickness of the negative electrode active material layer 20 is shown as T1. Of course, it can be understood that in some embodiments of the present application, the negative electrode active material layer 20 is disposed on one surface of the negative electrode current collector 10.
[0034] For example, the volume change rate of the first active material is 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between any two of the above numerical ranges. The second material layer on the surface layer of the negative electrode plate contains silicon element. The silicon-containing second active material has a large alternating expansion stress during the charge and discharge process of the secondary battery, which easily causes the negative electrode current collector to extend along its own length and width directions (hereinafter referred to as XY extension), increasing the possibility of deformation and wrinkling of the negative electrode plate. By selecting the first active material with a volume change rate within the scope of the present application and disposing it in the first material layer, the first material layer adjacent to the negative electrode current collector during the charge and discharge process of the secondary battery can relieve the influence of the alternating expansion stress of the silicon material particles on the negative electrode current collector, reducing the XY extension of the negative electrode current collector. If the volume change rate of the first active material is greater than 10%, the volume change rate of the first active material is too large to relieve the influence of the alternating expansion stress of the silicon material particles on the negative electrode current collector, and the XY extension of the negative electrode current collector is too large.
[0035] For example, T2 is 5, 5.3, 5.7, 6, 6.2, 6.6, 7, 7.5, 8 or any value between any two of the above numerical ranges. If T2 is less than 5, the single-layer thickness of the first material layer is too small to relieve the influence of the alternating expansion stress of the silicon material particles in the second material layer after lithium insertion on the negative electrode current collector, and the probability of improving the XY extension of the negative electrode current collector is relatively low; if T2 is greater than 8, the single-layer thickness of the first material layer is too large, resulting in too large a thickness of the negative electrode plate, and the secondary battery will suffer from energy density loss due to increased volume.
[0036] For example, the value of T2 / T1×100% is 4.6%, 5.0%, 5.2%, 5.6%, 6.0%, 6.3%, 6.5%, 6.7%, 7.0%, 7.2%, 7.5%, 7.7%, 8.0%, or any value between any two of the above numerical ranges. When the value of T2 / T1×100% is less than 4.6%, the single-layer thickness of the first material layer is too small relative to the total thickness of the negative electrode active material layer, which is insufficient to relieve the alternating expansion stress of the silicon material particles on the negative electrode current collector, and the probability of improving the XY extension of the negative electrode current collector is relatively low; when the value of T2 / T1×100% is greater than 8.0%, the single-layer thickness of the first material layer is too large relative to the total thickness of the negative electrode active material layer, and there will be a surplus in the content of the first active material beyond relieving the alternating expansion stress of the silicon material particles on the negative electrode current collector. When the total thickness of the negative electrode active material layer is fixed, the single-layer thickness of the second material layer will decrease accordingly, and the content of the second active material containing silicon in the negative electrode active material layer will decrease, which will reduce the capacity of the negative electrode active material layer and lower the capacity and energy density of the secondary battery.
[0037] Overall, the negative electrode tab provided in the first aspect of the present application is configured by disposing a first material layer containing a first active material with a relatively small volume change rate between the negative electrode current collector and the second material layer containing a silicon element, and regulating the volume change rate of the first active material, the single-layer thickness of the first material layer, and the ratio of the single-layer thickness of the first material layer to the total thickness of the negative electrode active material layer within the scope of the present application. During the charge and discharge process of the secondary battery, the lithium intercalation expansion of the first active material is small, the expansion stress of the first material layer is reduced, and it can better improve the influence of the alternating expansion stress of the second active material particles containing silicon on the XY extension of the negative electrode current collector. The tensile stress on the negative electrode current collector in its length direction and width direction is reduced, and the XY extension of the negative electrode current collector is improved. In this way, the possibility of deformation and wrinkling of the negative electrode tab is reduced, thereby improving the bonding state between the negative electrode tab and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the obstruction of the lithium ion passage caused by the loss of bonding between the negative electrode tab and the separator. In addition, the cooperation between the first material layer and the second material layer can also reduce the energy density loss brought by the first active material, and the capacity of the second active material can be fully exerted, so that the negative electrode active material layer has a higher capacity. As a result, the purple spot phenomenon at the head and tail of the negative electrode tab can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, the secondary battery has a high energy density. It can also relieve the safety problem of leakage caused by the XY extension of the negative electrode current collector piercing the outer package.
[0038] There is no particular limitation on the regulation method of the volume change rate of the first active material in the present application, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating the type of the first active material, or by regulating the size of the first active material.
[0039] In some embodiments of the present application, based on the mass of the negative electrode active material layer, the mass percentage of the first active material is W1, and 6.5% ≤ W1 ≤ 8.5%. For example, W1 is 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.7%, 8.0%, 8.2%, 8.5% or any value between any two of the above numerical ranges. Controlling the mass percentage of the first active material within the above range is beneficial to alleviating the influence of the alternating expansion stress brought by the silicon material particles on the negative electrode current collector, so as to improve the XY extension of the negative electrode current collector. In this way, the possibility of the negative electrode sheet deforming and wrinkling is reduced, thereby improving the bonding state between the negative electrode sheet and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the obstruction of the lithium ion path caused by the loss of bonding between the negative electrode sheet and the separator. Therefore, the purple spot phenomenon at the head and tail of the negative electrode sheet can be alleviated. In addition, when the mass percentage of the first active material is controlled within the above range, the first active material has little influence on the capacity of the negative electrode sheet, which is beneficial to the improvement of the energy density of the secondary battery.
[0040] In some embodiments of the present application, based on the mass of the negative electrode active material layer, the mass percentage of silicon element is W2, and 0.4 ≤ W2 / W1 ≤ 4.6. For example, the value of W2 / W1 is 0.4, 0.7, 1.0, 1.4, 1.6, 2.0, 2.5, 2.7, 3.0, 3.4, 3.6, 4.0, 4.4, 4.6 or any value between any two of the above numerical ranges. Under the same content of the first active material, the lower the content of the silicon element, the more obvious the improvement effect of the XY extension of the negative electrode current collector. Controlling the value of the ratio W2 / W1 of the mass percentage of the silicon element in the negative electrode active material layer to the mass percentage of the first active material within the above range, the alternating expansion stress brought by the silicon element can be alleviated by the first active material, which is beneficial to reducing the tensile stress suffered by the negative electrode current collector in its length direction and width direction, and improving the XY extension of the negative electrode current collector. In this way, the possibility of the negative electrode sheet deforming and wrinkling is reduced, thereby improving the bonding state between the negative electrode sheet and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the obstruction of the lithium ion path caused by the loss of bonding between the negative electrode sheet and the separator. It is also beneficial to reducing the energy density loss brought by the first active material, and beneficial to the second active material containing silicon element to provide a higher capacity for the negative electrode active material layer. Therefore, the purple spot phenomenon at the head and tail of the negative electrode sheet can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, the secondary battery has a higher energy density.
[0041] The present application has no special limitation on W2, as long as the purpose of the present application can be achieved. For example, 2.6% ≤ W2 ≤ 39.1%.
[0042] In some embodiments of the present application, 1.4 ≤ W2 / W1 ≤ 3.6. For example, the value of W2 / W1 is 1.4, 1.6, 2.0, 2.5, 2.7, 3.0, 3.4, 3.6, or any value between any two of the above numerical ranges. Controlling the value of the ratio W2 / W1 of the mass percentage content of silicon element in the negative electrode active material layer to the mass percentage content of the first active material within the above range is beneficial to better relieve the expansion stress brought by the silicon element, so as to further improve the XY extension of the negative electrode current collector. In this way, the possibility of deformation and wrinkling of the negative electrode plate is further reduced, thereby improving the bonding state between the negative electrode plate and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the blockage of the lithium ion path caused by the loss of bonding between the negative electrode plate and the separator. It is also beneficial to make the negative electrode active material layer have a higher capacity. Therefore, the purple spot phenomenon at the head and tail of the negative electrode plate can be further relieved, and on the basis of improving the kinetic performance of the secondary battery, the secondary battery has a higher energy density.
[0043] In some embodiments of the present application, the types of the first active material include at least one of lithium titanate, titanium dioxide, carbon nanotubes, or graphene. When lithium ions are inserted into or extracted from the spinel structure of lithium titanate (chemical formula Li4Ti5O 12 ), the lattice constant and volume change are very small, less than 1%. This "zero strain property" can avoid the destruction of the structure due to the back-and-forth expansion and contraction of the electrode material. During the lithium intercalation process of titanium dioxide (TiO2), a two-phase lattice transformation from tetragonal to orthorhombic occurs, and this process is accompanied by a lattice expansion of nearly 4%. The flexibility and unique one-dimensional characteristics of the carbon nanotube structure make it exhibit a very low volume expansion rate during the lithium intercalation process. Graphene is a material composed of a single layer of carbon atoms, with extremely high electrical conductivity and strength. Its two-dimensional structure can relieve volume expansion and has a low lithium intercalation expansion rate. Therefore, the above types of the first active material have a low volume change rate. Selecting the above types of the first active material for the first material layer can relieve the alternating expansion stress brought by the second active material containing silicon element, reduce the tensile stress on the negative electrode current collector in its length direction and width direction, and improve the XY extension of the negative electrode current collector. In this way, the possibility of deformation and wrinkling of the negative electrode plate is reduced, thereby improving the bonding state between the negative electrode plate and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the blockage of the lithium ion path caused by the loss of bonding between the negative electrode plate and the separator. Therefore, the purple spot phenomenon at the head and tail of the negative electrode plate can be relieved. It can also relieve the safety problem of leakage caused by the XY extension of the negative electrode current collector piercing the outer package.
[0044] In some embodiments of the present application, the types of the second active material include at least one of silicon carbide compounds, silicon oxide compounds, or pure silicon. The silicon carbide compound is a silicon carbide composite material. Based on the mass of the silicon carbide composite material, the mass percentage content of silicon element is 30% to 70%, and the mass percentage content of carbon element is 30% to 70%. The present application has no particular limitation on the silicon carbide composite material as long as the purpose of the present application can be achieved. For example, the silicon carbide composite material can be a composite material obtained by deposition. Exemplarily, the silicon carbide composite material can be a composite material with silicon material deposited on a carbon skeleton, or a composite material with carbon material deposited on a silicon skeleton. The silicon oxide compound includes SiOx, where 0 < x < 2. Exemplarily, the silicon oxide compound can include silicon monoxide (SiO, the molar ratio of silicon to oxygen is 1:1). The second active materials of the above types can provide a relatively high capacity for the negative electrode sheet, enabling the secondary battery to have a relatively high capacity and energy density.
[0045] In some embodiments of the present application, the second material layer includes a second active material and a carbon material. The present application has no particular limitation on the type and content of the carbon material as long as the purpose of the present application can be achieved. For example, the carbon material includes but is not limited to at least one of artificial graphite, natural graphite, hard carbon, soft carbon, or mesocarbon microbeads.
[0046] In some embodiments of the present application, the particle sizes of lithium titanate and titanium dioxide each independently satisfy: 1.1 μm ≤ Dv90 ≤ 1.5 μm, 0.7 μm ≤ Dv50 ≤ 1.0 μm; the length of the carbon nanotubes is from 0.1 μm to 1.0 μm; the sheet diameter of graphene is from 0.5 μm to 1.0 μm. For example, the Dv90 of the particle size of lithium titanate is 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any value between any two of the above numerical ranges. For example, the Dv50 of the particle size of lithium titanate is 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value between any two of the above numerical ranges. For example, the Dv90 of the particle size of titanium dioxide is 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any value between any two of the above numerical ranges. For example, the Dv50 of the particle size of titanium dioxide is 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value between any two of the above numerical ranges. For example, the length of the carbon nanotubes is 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value between any two of the above numerical ranges. For example, the sheet diameter of graphene is 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value between any two of the above numerical ranges. By controlling the particle sizes of lithium titanate and titanium dioxide, the length of the carbon nanotubes, and the sheet diameter of graphene within the above ranges, lithium titanate, titanium dioxide, carbon nanotubes, and graphene all have relatively high ionic conductivity and a large number of active sites. When used as the first active material in the first material layer, it is beneficial to further relieve the alternating expansion stress caused by the second active material containing silicon, so as to further improve the XY extension of the negative electrode current collector. In this way, the possibility of deformation and wrinkling of the negative electrode sheet is reduced, thereby improving the bonding state between the negative electrode sheet and the separator, and reducing the probability of purple spot phenomenon caused by the obstruction of the lithium ion path due to the loss of bonding between the negative electrode sheet and the separator and insufficient lithium intercalation at the interface. It is also beneficial to reduce the loss of energy density caused by the first active material. Therefore, the purple spot phenomenon at the head and tail of the negative electrode sheet can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, the secondary battery has a relatively high energy density. It can also relieve the safety problem of leakage caused by the XY extension of the negative electrode current collector piercing the outer package.
[0047] In the present application, Dv90 refers to the particle size at which, in the particle size distribution based on volume, starting from the small particle size side, the cumulative volume reaches 90%; Dv50 refers to the particle size at which, in the particle size distribution based on volume, starting from the small particle size side, the cumulative volume reaches 50%. The above-mentioned "particles" can be lithium titanate particles or titanium dioxide particles.
[0048] There is no particular limitation on the method for regulating the particle sizes of lithium titanate and titanium dioxide in this application, as long as the object of this application can be achieved. For example, it can be achieved by means of crushing and screening. There is no particular limitation on the method for regulating the length of carbon nanotubes in this application, as long as the object of this application can be achieved. For example, it can be achieved by means of crushing and screening. There is no particular limitation on the method for regulating the sheet diameter of graphene in this application, as long as the object of this application can be achieved. For example, the centrifugal screening method can be used to utilize the action of centrifugal force to separate according to the size of the graphene sheet diameter, and the graphene within the required sheet diameter range of this application can be screened out.
[0049] In some embodiments of this application, the lithium intercalation potential of the first active material is U, where 0.13V ≤ U ≤ 1.60V. Preferably, 0.97V ≤ U ≤ 1.60V. For example, the lithium intercalation potential U of the first active material is 0.13V, 0.18V, 0.22V, 0.27V, 0.33V, 0.40V, 0.51V, 0.60V, 0.70V, 0.80V, 0.90V, 1.00V, 1.08V, 1.21V, 1.30V, 1.42V, 1.50V, 1.60V, or any value between any two of the above numerical ranges. By regulating the lithium intercalation potential of the first active material within the above range, during the charge and discharge process of the secondary battery, it is beneficial for the first active material to preferentially undergo small lithium intercalation expansion, so as to relieve the larger lithium intercalation expansion brought by the silicon-containing second active material, thereby reducing the tensile stress on the negative electrode current collector in the length and width directions caused by the alternating expansion stress brought by the second active material particles, and improving the XY extension of the negative electrode current collector. In this way, the possibility of the negative electrode sheet deforming and wrinkling is reduced, thereby being able to improve the bonding state between the negative electrode sheet and the separator, and reducing the probability of purple spot phenomenon caused by the blockage of the lithium ion path due to the loss of bonding between the negative electrode sheet and the separator, resulting in insufficient lithium intercalation at the interface. Thus, the purple spot phenomenon at the head and tail of the negative electrode sheet can be alleviated. It can also relieve the safety problem of the XY extension of the negative electrode current collector piercing the outer package and causing liquid leakage.
[0050] There is no particular limitation on the method for regulating the lithium intercalation potential of the first active material in this application, as long as the object of this application can be achieved. For example, it can be achieved by regulating the type and particle size of the first active material.
[0051] In some embodiments of this application, the specific surface areas of lithium titanate and titanium dioxide in the first active material are each independently 3.1m 2 / g to 8.2m 2 / g, and the specific surface areas of graphene and carbon nanotubes in the first active material are each independently 15m 2 / g to 220m 2 / g. For example, the specific surface area of lithium titanate is 3.1m 2 / g, 3.6m2 / g, 4.0 m 2 / g, 4.5 m 2 / g, 5.1 m 2 / g, 5.6 m 2 / g, 6.0 m 2 / g, 6.6 m 2 / g, 7.3 m 2 / g, 8.2 m 2 / g or any value within any two of the above numerical ranges. For example, the specific surface area of titanium dioxide is 3.1 m 2 / g, 3.6 m 2 / g, 4.0 m 2 / g, 4.5 m 2 / g, 5.1 m 2 / g, 5.6 m 2 / g, 6.0 m 2 / g, 6.6 m 2 / g, 7.3 m 2 / g, 8.2 m 2 / g or any value within any two of the above numerical ranges. For example, the specific surface area of graphene is 15 m 2 / g, 40 m 2 / g, 50 m 2 / g, 65 m 2 / g, 90 m 2 / g, 110 m 2 / g, 130 m 2 / g, 156 m 2 / g, 183 m 2 / g, 200 m 2 / g, 220 m 2 / g or any value within any two of the above numerical ranges. For example, the specific surface area of carbon nanotubes is 15 m 2 / g, 40 m 2 / g, 50 m 2 / g, 65 m 2 / g, 90 m 2 / g, 110 m 2 / g, 130 m 2 / g, 156 m 2 / g, 183 m 2 / g, 200 m 2 / g, 220 m 2 / g or any value between any two of the above numerical ranges. Controlling the specific surface areas of lithium titanate, titanium dioxide, carbon nanotubes, and graphene within the above ranges is beneficial for the first active material to have more active sites during the reaction process, thereby improving the reaction activity of the first active material. It is also beneficial for alleviating the expansion of the alternating stress brought by the second active material to improve the XY extension of the negative electrode current collector. The first active material also provides a small amount of capacity, which is beneficial for increasing the volume energy density of the secondary battery. In this way, the possibility of deformation and wrinkling of the negative electrode sheet is reduced, thereby improving the bonding state between the negative electrode sheet and the separator, and reducing the probability of purple spot phenomenon caused by insufficient interfacial lithium intercalation due to the blockage of the lithium ion path caused by the loss of bonding between the negative electrode sheet and the separator. The secondary battery can have a high energy density. As a result, the purple spot phenomenon at the head and tail of the negative electrode sheet can be alleviated, and on the basis of improving the kinetic performance of the secondary battery, the secondary battery has a high energy density. It can also alleviate the safety problem of leakage caused by the XY extension of the negative electrode current collector piercing the outer package.
[0052] The present application has no particular limitation on the method of controlling the specific surface area of the first active material, as long as the purpose of the present application can be achieved. For example, the specific surface area can be controlled by controlling the particle sizes of lithium titanate and titanium dioxide, the specific surface area can be controlled by controlling the length of the carbon nanotubes, and the specific surface area can be controlled by controlling the sheet diameter of the graphene. Generally speaking, the larger the particle sizes of lithium titanate and titanium dioxide, the smaller their respective specific surface areas; the smaller the particle sizes of lithium titanate and titanium dioxide, the larger their respective specific surface areas. The longer the length of the carbon nanotubes, the smaller their specific surface area; the shorter the length of the carbon nanotubes, the larger their specific surface area. The larger the sheet diameter of the graphene, the smaller its specific surface area; the smaller the sheet diameter of the graphene, the larger its specific surface area.
[0053] In some embodiments of the present application, the powder conductivity of lithium titanate is α1, 2×10 -6 S / m ≤ α1 ≤ 1×10 - 4 S / m; the powder conductivity of titanium dioxide is α2, 3×10 -14 S / m ≤ α2 ≤ 3×10 -10 S / m; the powder conductivity of graphene is α3, 3×10 6 S / m ≤ α3 ≤ 1×10 8 S / m; the powder conductivity of carbon nanotubes is α4, 3×10 6 S / m ≤ α4 ≤ 1×10 8 S / m. For example, the powder conductivity α1 of lithium titanate is 2×10 -6 S / m, 5×10 -6 S / m, 1×10 -5 S / m, 3×10 -5S / m, 8×10 -5 S / m, 1×10 -4 S / m or any value between any two of the above numerical ranges. For example, the powder conductivity α2 of titanium dioxide is 3×10 - 14 S / m, 9×10 -14 S / m, 4×10 -13 S / m, 7×10 -13 S / m, 1×10 -12 S / m, 5×10 -12 S / m, 2×10 -11 S / m, 6×10 -11 S / m, 3×10 -10 S / m or any value between any two of the above numerical ranges. For example, the powder conductivity α3 of graphene is 3×10 6 S / m, 9×10 6 S / m, 4×10 7 S / m, 7×10 7 S / m, 1×10 8 S / m or any value between any two of the above numerical ranges. For example, the powder conductivity α4 of carbon nanotubes is 3×10 6 S / m, 9×10 6 S / m, 4×10 7 S / m, 7×10 7 S / m, 1×10 8 S / m or any value between any two of the above numerical ranges. The powder conductivities of lithium titanate, titanium dioxide, carbon nanotubes, and graphene are within the above ranges, which can accelerate the electron transfer speed, make the negative electrode reaction in the secondary battery more rapid during charge and discharge, thereby improving the charge and discharge efficiency of the secondary battery and reducing energy loss; it can also reduce the polarization phenomenon in the secondary battery during charge and discharge, reduce the stress and strain of the negative electrode active material, thereby improving the cycle stability of the secondary battery and extending the service life of the secondary battery.
[0054] The present application has no particular limitation on the method of regulating the powder conductivity of the first active material, as long as the object of the present application can be achieved. For example, different commercially available first active materials with different powder conductivities can be purchased, and the powder conductivity of the first active material can be determined by combining the test method of "testing the powder conductivity" in the present application, and the first active material with the required powder conductivity can be selected. Or, the regulation of the powder conductivity can be achieved by adjusting the size of the first active material. Generally speaking, the larger the size of the first active material, the smaller the powder conductivity; the smaller the size of the first active material, the larger the powder conductivity. It should be noted that the "size" in the present application can be the particle size of lithium titanate and titanium dioxide, the length of carbon nanotubes, and the sheet diameter of graphene.
[0055] In some embodiments of the present application, the powder lithium ion diffusion coefficient of lithium titanate and titanium dioxide is δ1, 1.25×10 -9 cm 2 / s ≤ δ1 ≤ 3×10 -7 cm 2 / s; the powder lithium ion diffusion coefficient of graphene and carbon nanotubes is δ2, 1×10 -7 cm 2 / s ≤ δ2 ≤ 1×10 -4 cm 2 / s. For example, the powder lithium ion diffusion coefficient of lithium titanate is 1.25×10 -9 cm 2 / s, 5×10 -9 cm 2 / s, 7×10 -9 cm 2 / s, 2×10 -8 cm 2 / s, 6×10 -8 cm 2 / s, 1×10 -7 cm 2 / s, 3×10 -7 cm 2 / s or any value between any two of the above numerical ranges. For example, the powder lithium ion diffusion coefficient of titanium dioxide is 1.25×10 -9 cm 2 / s, 5×10 -9 cm 2 / s, 7×10 -9 cm 2 / s, 2×10 -8 cm 2 / s, 6×10 -8 cm 2 / s, 1×10 -7 cm 2 / s, 3×10 -7 cm 2 / s or any value between any two of the above numerical ranges. For example, the powder lithium ion diffusion coefficient of graphene is 1×10 -7 cm 2 / s, 5×10 -7 cm 2 / s, 7×10 -7 cm 2 / s, 2×10 -6 cm 2 / s, 8×10 -6 cm 2 / s, 1×10 -5 cm2 / s, 5×10 -5 cm 2 / s, 1×10 - 4 cm 2 / s or any value within any two of the above numerical ranges. For example, the powder lithium-ion diffusion coefficient of carbon nanotubes is 1×10 -7 cm 2 / s, 5×10 -7 cm 2 / s, 7×10 -7 cm 2 / s, 2×10 -6 cm 2 / s, 8×10 -6 cm 2 / s, 1×10 -5 cm 2 / s, 5×10 - 5 cm 2 / s, 1×10 -4 cm 2 / s or any value within any two of the above numerical ranges. The powder lithium-ion diffusion coefficients of lithium titanate, titanium dioxide, carbon nanotubes, and graphene are within the above range, and lithium ions have a good diffusion rate in the secondary battery, which is beneficial to improving the purple spot phenomenon at the head and tail of the negative electrode tab and is also beneficial to improving the cycle performance of the secondary battery using the negative electrode tab of the present application.
[0056] In some embodiments of the present application, the carbon nanotubes may be at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, or few-walled carbon nanotubes. Preferably, the carbon nanotubes of the present application are single-walled carbon nanotubes.
[0057] The present application does not particularly limit the method of regulating the powder lithium-ion diffusion coefficient of the first active material, as long as the purpose of the present application can be achieved. For example, different commercially available first active materials with different powder lithium-ion diffusion coefficients can be purchased, and the powder conductivity of the first active material can be determined by combining with the test method of "testing the powder lithium-ion diffusion coefficient" in the present application, and the first active material with the required powder lithium-ion diffusion coefficient can be selected. Or, the powder conductivity can be regulated by adjusting the size of the first active material. Generally speaking, the larger the size of the first active material, the smaller the powder lithium-ion diffusion coefficient; the smaller the size of the first active material, the larger the powder lithium-ion diffusion coefficient.
[0058] In some embodiments of the present application, the first Coulombic efficiency of the first active material is E, where 60% < E ≤ 85%. Preferably, 75% ≤ E ≤ 80%. For example, the first Coulombic efficiency E of the first active material is 60.1%, 62%, 67%, 71%, 75%, 78%, 82%, 85%, or any value between any two of the above numerical ranges. The first Coulombic efficiency E of the first active material being within the above range indicates that the first active material has a high first Coulombic efficiency, the capacity of the first active material has a high utilization rate, which is beneficial for the secondary battery to have a high energy density, and the capacity attenuation rate of the secondary battery during subsequent charge and discharge cycles is also slow, which is beneficial for extending the cycle life of the secondary battery.
[0059] The present application does not particularly limit the method of regulating the first Coulombic efficiency E of the first active material, as long as the purpose of the present application can be achieved. For example, it can be achieved by adjusting the type and size of the first active material. Generally speaking, the smaller the size of the first active material, the larger the specific surface area of the first active material, the more side reactions it has with the electrolyte, and the smaller the first Coulombic efficiency of the first active material.
[0060] In some embodiments of the present application, the adhesion between the first material layer and the negative electrode current collector is N1, where 26.5 N / m ≤ N1 ≤ 55 N / m. For example, the adhesion N1 between the first material layer and the negative electrode current collector is 26.5 N / m, 28 N / m, 32 N / m, 38 N / m, 42 N / m, 46 N / m, 52 N / m, 55 N / m, or any value between any two of the above numerical ranges. The adhesion N1 between the first material layer and the negative electrode current collector being within the above range indicates that there is a high adhesion between the first material layer and the negative electrode current collector. During the charge and discharge cycles of the secondary battery, due to the expansion of the silicon-containing material, the risk of the first material layer peeling off from the negative electrode current collector is low, and the negative electrode tab and the separator can also have a good bonding state. In this way, the purple spot phenomenon at the head and tail of the negative electrode tab can be alleviated, and the safety risk of the secondary battery can also be reduced.
[0061] The present application does not particularly limit the method of regulating the adhesion N1 between the first material layer and the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can be achieved by adjusting the type and content of the binder in the first material layer and adjusting the content of the second active material containing silicon elements in the second material layer.
[0062] In some embodiments of the present application, the negative electrode current collector includes any one of a copper current collector, a copper foam current collector, a nickel current collector, or a stainless steel current collector. The negative electrode current collectors of the above types are applied to the negative electrode sheet, the XY extension of the negative electrode current collector can be improved, and the probability of purple spots appearing at the head and tail of the negative electrode sheet and piercing the outer package to cause liquid leakage is reduced. The capacity of the negative electrode active material layer can be fully exerted, so that the secondary battery has a high energy density.
[0063] In some embodiments of the present application, the peel force between the first material layer and the second material layer is N2, and 16.7 N / m ≤ N2 ≤ 46.2 N / m. For example, the peel force N2 is 16.7 N / m, 18.2 N / m, 20.0 N / m, 23.7 N / m, 27.0 N / m, 28.5 N / m, 31.2 N / m, 35.0 N / m, 36.7 N / m, 40.0 N / m, 42.6 N / m, 46.2 N / m, or any value between any two of the above numerical ranges. When the peel force between the first material layer and the second material layer is within the above range, it indicates that the peel force level of the negative electrode sheet is moderate, the probability of the first material layer and the second material layer peeling off the film is low, and it can also reduce the probability of the capacity of the negative electrode sheet being lost due to excessive addition of the binder in the first material layer and the second material layer.
[0064] The present application has no particular limitation on the regulation method of the peel force N2 between the first material layer and the second material layer, as long as the purpose of the present application can be achieved. For example, it can be achieved by adjusting the content and type of the binder in the negative electrode active material layer and adjusting the content of the second active material containing silicon elements in the second material layer.
[0065] In some embodiments of the present application, the resistivity of the negative electrode sheet in the thickness direction is Z, and 3.7 Ω·cm ≤ Z ≤ 15.2 Ω·cm. Preferably, 4.7 Ω·cm ≤ Z ≤ 5.2 Ω·cm. For example, the resistivity Z of the negative electrode sheet in the thickness direction is 3.7 Ω·cm, 5.0 Ω·cm, 7.7 Ω·cm, 9.0 Ω·cm, 12.0 Ω·cm, 13.7 Ω·cm, 14.4 Ω·cm, 15.2 Ω·cm, or any value between any two of the above numerical ranges. When the resistivity Z of the negative electrode sheet is within the above range, it is beneficial to the transport of lithium ions in the negative electrode sheet, which is beneficial to alleviating the purple spot phenomenon at the head and tail of the negative electrode sheet and is also beneficial to improving the cycle performance of the secondary battery.
[0066] The present application has no particular limitation on the regulation method of the resistivity Z of the negative electrode sheet in the thickness direction, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating the types and particle sizes of the first active material and the second active material.
[0067] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the object of the present application can be achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm. Optionally, the first material layer may further include at least one of a negative electrode conductive agent, a dispersant, or a negative electrode binder. The second material layer may further include at least one of a negative electrode conductive agent, a dispersant, or a negative electrode binder. The present application has no particular limitation on the types of the negative electrode conductive agent, the dispersant, and the negative electrode binder in the first material layer and the second material layer, as long as the object of the present application can be achieved. The present application has no particular limitation on the mass ratios of the negative electrode conductive agent, the dispersant, and the negative electrode binder in the first material layer and the second material layer, as long as the object of the present application can be achieved. The present application has no particular limitation on the content of the second active material, as long as the object of the present application can be achieved. For example, based on the mass of the negative electrode active material layer, the mass percentage content of the first active material is 6.5% to 8.5%, the mass percentage content of the second active material is 4.9% to 85.4%, the mass percentage content of the carbon material is 4.4% to 87.3%, the mass percentage content of the negative electrode conductive agent is 0.2% to 0.3%, the mass percentage content of the dispersant is 0.3% to 0.4%, and the mass percentage content of the negative electrode binder is 0.8% to 1.0%.
[0068] The present application has no particular limitation on the method for preparing the negative electrode plate, as long as the object of the present application can be achieved. For example, in some embodiments of the present application, the method for preparing the negative electrode plate includes, but is not limited to, the following steps: (1) preparing a first material layer slurry and a second material layer slurry; (2) uniformly coating the first material layer slurry on one surface of the negative electrode current collector, drying to form the first material layer, and then uniformly coating the second material layer slurry on the surface of the first material layer away from the negative electrode current collector, drying to form the second material layer, thereby obtaining a semi-finished negative electrode plate with a single-sided coated negative electrode active material layer; (3) repeating step (2) on the other surface of the negative electrode current collector to obtain a semi-finished negative electrode plate with a double-sided coated negative electrode active material layer, and then obtaining the negative electrode plate after cold pressing and slitting. In some other embodiments of the present application, the semi-finished negative electrode plate may also be cold pressed and slit after step (2) to obtain a negative electrode plate with a single-sided coated negative electrode active material layer.
[0069] The second aspect of the present application provides a secondary battery, which includes the negative electrode plate described in any of the foregoing embodiments. Therefore, the secondary battery has good kinetic performance and a high energy density.
[0070] In some embodiments of the present application, the secondary battery includes a positive electrode tab. The present application places no particular limitation on the positive electrode tab, as long as the object of the present application can be achieved. In one embodiment, the positive electrode tab includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is disposed on one or both surfaces of the positive electrode current collector. The above-mentioned "surface" may be a partial surface or the entire surface of the positive electrode current collector. The present application places no particular limitation on the positive electrode current collector, as long as the object of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil, or the like. The positive electrode active material layer of the present application contains a positive electrode active material. The present application places no particular limitation on the type of the positive electrode active material, as long as the object of the present application can be achieved. For example, the positive electrode active material may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium iron phosphate, lithium-rich manganese-based material, lithium cobalt oxide, lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate. In the present application, the positive electrode active material may further contain a non-metallic element, and the non-metallic element may include at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur, and these elements can further improve the stability of the positive electrode active material. In the present application, there is no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the object of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm. The thickness of a single-layer positive electrode active material layer is 30 μm to 120 μm. Optionally, the positive electrode active material layer may further include at least one of a positive electrode conductive agent or a positive electrode binder. The present application places no particular limitation on the types of the positive electrode conductive agent and the positive electrode binder in the positive electrode active material layer, as long as the object of the present application can be achieved. The present application places no particular limitation on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can select according to actual needs, as long as the object of the present application can be achieved. For example, based on the mass of the positive electrode active material layer, the mass percentage content of the positive electrode active material is 97.5% to 98.9%, the mass percentage content of the positive electrode conductive agent is 0.8% to 1.7%, and the mass percentage content of the positive electrode binder is 0.6% to 1.0%.
[0071] In some embodiments of the present application, the secondary battery further includes a separator disposed between the positive electrode plate and the negative electrode plate to separate the positive electrode plate and the negative electrode plate, prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and not affect the progress of the electrochemical charge and discharge process. The present application places no particular limitation on the separator, as long as it can achieve the purpose of the present application. For example, the material of the separator may include, but is not limited to, at least one of polyolefins (PO) mainly composed of polyethylene (PE) and polypropylene (PP), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of the separator may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a rolled film, or a spun film. The present application places no particular limitation on the thickness of the separator, as long as it can achieve the purpose of the present application.
[0072] In some embodiments of the present application, the secondary battery further includes an electrolyte. The present application places no particular limitation on the electrolyte, as long as it can achieve the purpose of the present application. The secondary battery includes an outer package, and the negative electrode plate, the positive electrode plate, the separator, and the electrolyte are accommodated in the outer package. The present application places no particular limitation on the outer package, as long as it can achieve the purpose of the present application.
[0073] The secondary battery of the present application is not particularly limited, and it may include any device that undergoes an electrochemical reaction. For example, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0074] The present application places no particular limitation on the preparation method of the secondary battery, and a preparation method well-known in the art may be selected, as long as it can achieve the purpose of the present application. For example, the preparation method of the secondary battery includes, but is not limited to, the following steps: stacking the separator, the positive electrode plate, the separator, and the negative electrode plate in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly, placing the electrode assembly into the outer package, injecting the electrolyte into the outer package and sealing it to obtain the secondary battery; or stacking the separator, the positive electrode plate, the separator, and the negative electrode plate in sequence, and then fixing the four corners of the entire laminated structure to obtain a laminated electrode assembly, placing the electrode assembly into the outer package, injecting the electrolyte into the outer package and sealing it to obtain the secondary battery.
[0075] The third aspect of the present application provides an electronic device, which includes the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device has good performance in use.
[0076] The electronic device of the present application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to: laptop computers, pen-input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, liquid crystal televisions, hand-held cleaners, portable CD players, minidiscs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors.
[0077] Examples
[0078] Hereinafter, examples and comparative examples will be given to more specifically illustrate the embodiments of the present application. Various tests and evaluations are carried out according to the following methods.
[0079] Testing method and device:
[0080] Sampling method for the negative electrode plate:
[0081] Dismantle a lithium-ion battery that has been discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, take out the negative electrode plate, soak it in dimethyl carbonate (DMC) for 20 minutes, and then rinse it once with DMC and once with acetone in sequence. Then place the negative electrode plate in an oven and bake it at 80°C for 12 hours to obtain a processed negative electrode plate sample. It can be understood that when the voltage range marked on the outer package of the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. Unless otherwise specified, the charging cut-off voltage of the lithium-ion battery as an example in the present application is 4.45V and the discharging cut-off voltage is 3.0V.
[0082] Unless otherwise specified, the negative electrode plates used in the following test methods are obtained by the above method.
[0083] Sampling method for the first active material:
[0084] Take the negative electrode sheet obtained by the aforementioned method and use plasma polishing technology to polish starting from the upper layer of the negative electrode sheet. After polishing away 90% of the total thickness of the negative active material layer, the remaining material layer on the surface of the negative current collector is the first material layer. After scraping the substances of the remaining material layer from the negative current collector, the first active material is obtained by differential centrifugation. Specifically: Make the substances of the first material layer into a suspension with a concentration of 0.1 g / mL. Under the action of gravity or centrifugal force, different substance particles settle, and according to the sedimentation rates of different substance particles, different substances in the first material layer are separated. The method for preparing the above suspension: Add 100 g of the substances of the first material layer to 1.0 L of deionized water, and under ice bath conditions, use a homogenizer to break up the substances of the first material layer to form a uniform suspension with a concentration of 0.1 g / mL.
[0085] Elemental analysis is carried out on the different substances separated above. The one containing Ti element is the first active material, and the products after lithium intercalation of lithium titanate and titanium dioxide are Li7Ti5O 12 and Li y TiO2 (2 ≤ y ≤ 3.5). It is possible to confirm which specific substance the first active material is by observing the microscopic morphology and size changes of the material after lithium intercalation. Among them, Li7Ti5O 12 usually maintains a good particle morphology, while Li y TiO2 will show obvious volume expansion. If it does not contain Ti element, scanning electron microscopy is used for morphology analysis to distinguish the carbon nanotubes and graphene used as the first active material. Graphene is a two-dimensional sheet structure, usually showing a veil-like or wrinkled sheet layer, and carbon nanotubes are one-dimensional materials, presenting a hollow tubular structure with a hollow interior.
[0086] Unless otherwise specified, the first active material used in the following test methods is obtained by the above method.
[0087] Assembly of the half-cell:
[0088] Take 7 g of the first active material obtained by the aforementioned method, 0.5 g of the binder polyacrylic acid, and 0.5 g of the conductive agent single-walled carbon nanotubes, stir and prepare them into a first material layer slurry with a solid content of 38 wt%. Coat the first material layer slurry on the surface of the copper current collector, and the coating areal density is 6 mg / 1540.25 mm 2 , and dry it at 120 °C to form the first material layer; Take 20 g of silicon-carbon powder, 75 g of graphite powder, 5 g of the binder polyacrylic acid, and 5 g of the conductive agent single-walled carbon nanotubes, stir and prepare them into a second material layer slurry with a solid content of 42 wt%. Coat the second material layer slurry on the surface of the first material layer away from the copper current collector, and the coating areal density is 60 mg / 1540.25 mm 2, dried at 120 °C to form a second material layer; thus, a negative electrode sheet was prepared. The negative electrode sheet was cut into circular pieces with a diameter of 14 mm and used as electrodes. Lithium metal was used as the counter electrode. A separator was placed between the electrode and the counter electrode, and an electrolyte was injected to assemble a half-cell. The above-mentioned separator and electrolyte were the same as those in Example 1-1.
[0089] Unless otherwise specified, the half-cells used in the following test methods were obtained by the above method.
[0090] Test of the volume change rate of the first active material:
[0091] Install the measuring device: Install the half-cell in the battery fixture to ensure that the surface of the half-cell is aligned with the thickness measuring device. Calibrate the thickness measuring device and record the initial thickness of the half-cell.
[0092] Charge and discharge test: At 25 °C, use an electrochemical workstation to charge the half-cell at a constant current of 0.1C to 0.05V, then charge at a constant voltage of 0.05V to 0.025C, let it stand for 10 min, and then discharge at a constant current of 0.1C to 2.5V. Record the final thickness of the half-cell.
[0093] Volume change rate (%) of the first active material = (final thickness - initial thickness) / initial thickness × 100%.
[0094] Test of silicon element content:
[0095] Take the negative electrode sheet obtained by the above method. Scrape off the negative electrode active material layer from the negative electrode sheet and perform inductively coupled plasma mass spectrometry (ICP-MS) test to measure the content W2 of silicon element in the negative electrode active material layer. Among them, the test instrument used for ICP-MS test is the NexlON 350X inductively coupled plasma mass spectrometer of PerkinElmer.
[0096] Test of particle size, length and sheet diameter:
[0097] (1) Test of particle size:
[0098] Referring to the national standard GB / T 19077-2016 (Method for Laser Diffraction Particle Size Analysis), use a laser particle size analyzer (such as Malvern Master Size 3000) to measure the particle size Dv50 and Dv90 of the first active material.
[0099] (2) Test of length:
[0100] Take the negative electrode sheet and obtain the cross-section of the first material layer on the negative electrode sheet by brittle fracture with liquid nitrogen;
[0101] The cross-section was observed under a scanning electron microscope (SEM). Ten different positions were tested for the length of the carbon nanotubes, and the average value was taken as the target value. The number of carbon nanotubes tested was 30.
[0102] (3) Test of the sheet diameter:
[0103] Take the negative electrode sheet and obtain the cross-section of the first material layer on the negative electrode sheet by brittle fracture with liquid nitrogen.
[0104] The cross-section was observed under SEM. Ten different positions were tested for the sheet diameter of the graphene, and the average value was taken as the target value. The number of graphene sheets tested was 30.
[0105] Test of the specific surface area of the first active material:
[0106] Dry the first active material to be tested in a vacuum drying oven and then load it into a sample tube. Use a specific surface area analyzer (TristarⅡ3020M) to test the specific surface area of the first active material to be tested by the nitrogen adsorption / desorption method. Among them, the specific test is carried out according to "GB / T 19587-2017 Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0107] Test of the powder conductivity:
[0108] Take 5 g of the first active material and press it under a constant pressure of 5000 kg with an electronic press for 20 s to obtain a sample sheet. At this time, the area S of the sample sheet and the height h of the sample sheet are measured. Place the sample sheet between the electrodes of a resistance tester (Suzhou Jingge Electronics ST-2255A), apply a voltage U at both ends of the sample sheet, measure the current I, and obtain the sample sheet resistance R according to the formula R = U / I. Calculate the powder conductivity according to the formula α = h / (S×R) / 1000, and the unit is S / m.
[0109] Test of the powder lithium ion diffusion coefficient:
[0110] The constant current intermittent titration method was used to test the lithium ion diffusion coefficient, and the steps are as follows:
[0111] (1) Let the half-cell prepared by the aforementioned method stand at room temperature for 12 h; (2) Discharge at a constant current of 0.05C for 30 min. If the voltage is less than or equal to 0.005V, jump to step (4); (3) After standing for 2 h, jump to step (2); (4) Stand for 30 min; (5) Charge at a constant current of 0.05C for 30 min. If the voltage is greater than or equal to 3.0V, jump to step (7); (6) After standing for 2 h, jump to step (5); (7) Stand for 30 min; (8) If the number of cycles ≤ 3, jump to step (1); (9) End.
[0112] δ is calculated by the following formula: δ = (4 / πτ)(n m V m / S) 2 (ΔE s / ΔE t ) 2 , where: δ is the lithium-ion diffusion coefficient; τ is the relaxation time, i.e., the standing time mentioned above; n m is the number of moles of lithium ions; V m is the molar volume of the electrode material; S is the electrode / electrolyte contact area; ΔE s is the voltage change caused by the pulse; ΔE t is the voltage change during constant current charge (discharge).
[0113] Test of the first Coulombic efficiency E of the active material:
[0114] Select the half-cell prepared by the aforementioned method. Using an electrochemical workstation, charge the half-cell at a constant current of 0.1C to 0.05V, then charge it at a constant voltage of 0.05V to 0.025C, let it stand for 10 min, and then discharge it at a constant current of 0.1C to 2.5V. During the charge and discharge process in the voltage range of 0.05V to 2.5V, record the capacity change of the half-cell during charge and discharge in real time. The first Coulombic efficiency (%) = discharge capacity / charge capacity × 100%.
[0115] Test of the lithium intercalation potential U of the first active material:
[0116] Select the half-cell prepared by the aforementioned method. Using an electrochemical workstation, charge the half-cell at a constant current of 0.1C to 0.05V, then charge it at a constant voltage of 0.05V to 0.025C, let it stand for 10 min, and then discharge it at a constant current of 0.1C to 2.5V. During the charge and discharge process in the voltage range of 0.05V to 2.5V, record the voltage change of the half-cell during charge and discharge in real time. The lithium intercalation potential U is the obvious lithium intercalation platform potential during the charging of the aforementioned half-cell.
[0117] Test of the adhesion force N1 between the first material layer and the negative electrode current collector:
[0118] Take the negative electrode sheet sample, scrape off the negative electrode active material layer on one surface of the negative electrode current collector. For the negative electrode active material layer on the other surface of the negative electrode current collector, use plasma polishing technology to polish from the upper layer of the negative electrode sheet. After polishing 90% of the thickness of the negative electrode active material layer, the remaining part on the negative electrode current collector is the first material layer.
[0119] Then cut a test specimen with a width of 20 mm and a length of 160 mm. Use double-sided tape with a width of 20 mm and a length of 150 mm to paste the test specimen onto a steel plate with a width of 20 mm and a length of 300 mm, with the negative current collector facing the steel plate. Connect and fix a paper tape with the same width as the test specimen and a length of 200 mm to one end of the test specimen, and use a Gaotie AI-3000 tensile testing machine for testing. Fix the test specimen on the test bench, turn the paper tape up 180°, and fix it with a clamp. Then the tensile testing machine starts to pull the paper tape at a speed of 50 mm / min, and the tensile displacement is 50 mm. When the curve flattens and the displacement is greater than 10 mm, take the tensile force value to calculate the adhesion force between the first material layer and the negative current collector, unit: N / m.
[0120] After the adhesive tape peels off the first material layer, send the split negative electrode plate for SEM and energy dispersive spectrometer (EDS) analysis. If the surface of the copper foil does not contain the first active material, the test result at this time is the adhesion force N1 between the first material layer and the negative current collector. In other cases, retest until the above test result appears.
[0121] Test of peel force N2:
[0122] Take a sample of the negative electrode plate and scrape off the negative active material layer on one surface of the negative current collector. Then cut a test specimen of the negative electrode plate with a width of 20 mm and a length of 160 mm. Use double-sided tape with a width of 20 mm and a length of 150 mm to paste the test specimen onto a steel plate with a width of 20 mm and a length of 300 mm, with the negative current collector facing the steel plate. Connect and fix a paper tape with the same width as the test specimen and a length of 200 mm to one end of the test specimen, and use a Gaotie AI-3000 tensile testing machine for testing. Fix the test specimen on the test bench, turn the paper tape up 180°, and fix it with a clamp. Then the tensile testing machine starts to pull the paper tape at a speed of 50 mm / min, and the tensile displacement is 50 mm. When the curve flattens and the displacement is greater than 10 mm, take the tensile force value to calculate the peel force N2 between the first material layer and the second material layer, unit: N / m.
[0123] After the adhesive tape peels off the second material layer, send the split negative electrode plate for SEM and EDS analysis. If the surface of the negative electrode plate connected to the copper foil only contains the first active material and no second active material, and the surface of the negative electrode plate connected to the adhesive tape only contains the second active material and no first active material, the test result at this time is the peel force N2 between the first material layer and the second material layer. In other cases, retest until the above test result appears.
[0124] Test of resistivity Z of the negative electrode plate along the thickness direction:
[0125] Use a two-probe resistance tester for testing. Adjust the pressure between the two probes to 0.4 t. Place the negative electrode sheet sample to be tested in the middle of the probes, ensuring that the probes are in contact with the upper and lower surfaces of the negative electrode sheet (to measure the resistivity in the thickness direction of the negative electrode sheet). Run the instrument. After 5 seconds, record the internal resistance value shown on the resistance tester. Randomly test 20 different points according to the above method, and calculate the average value of the 20 recorded internal resistances, which is the resistivity Z of the negative electrode sheet along the thickness direction.
[0126] Test for the XY extension data of the negative current collector:
[0127] Charge the lithium-ion battery at a constant current of 1 C to 4.45 V in an environment of 25 ± 3 °C, then charge it at a constant voltage of 4.45 V to 0.025 C, and then discharge it at a constant current of 0.7 C to 3.0 V. This is one charge-discharge cycle. Test according to the above charge-discharge cycle. After 200 cycles, charge it at a constant current of 1 C to 4.45 V, and then charge it at a constant voltage of 4.45 V to 0.025 C. Disassemble and take out the negative electrode sheet, measure the copper foil width of the empty foil area as σ0, and measure the copper foil widths of the front end (head), middle end (middle part), and tail end (tail) of the area with the negative electrode active material layer as σ1, σ2, and σ3 respectively. It should be noted that when the disassembled negative electrode sheet is in the unfolded state, the side close to the winding center is the front end, the side far from the winding center is the tail end, and the middle end is located between the front end and the tail end. It can be understood that the winding center can be understood as the part clamped by the winding needle during the winding process of the lithium-ion battery.
[0128] Head XY elongation rate (%) = (σ1 - σ0) / σ0 × 100%;
[0129] Middle XY elongation rate (%) = (σ2 - σ0) / σ0 × 100%;
[0130] Tail XY elongation rate (%) = (σ3 - σ0) / σ0 × 100%;
[0131] Average XY elongation rate (%) = (Head elongation rate + Middle elongation rate + Tail elongation rate) / 3.
[0132] For each example and comparative example, 5 lithium-ion batteries are tested, and the average value of the test results of the 5 lithium-ion batteries is taken as the XY extension level of the current lithium-ion battery design.
[0133] Test for the purple spot area:
[0134] Place the lithium-ion battery in an incubator at 25°C and let it stand for 60 minutes to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to 4.45V at 25°C, then charge it at a constant voltage of 4.45V to 0.025C, let it stand for 5 minutes, and then discharge it at a constant current of 1C to 3.0V; this is one charge-discharge cycle. After 200 charge-discharge cycles, charge it at a constant current of 1C to 4.45V again, and then charge it at a constant voltage of 4.45V to 0.025C to obtain a fully charged battery after 200 cycles. Disassemble the lithium-ion battery in a drying room with a humidity less than 5%, and take pictures to record whether there are purple spots at the corner interface of the negative electrode sheet. After taking pictures, use 3D MAX to measure the area of the purple spots at both ends of the negative electrode sheet and the total area of the negative electrode sheet, and calculate the percentage S of the purple spot area in the negative electrode sheet area. If S≤0.01%, record it as "no purple spots"; if 0.01%<S≤0.5%, record it as "slight purple spots"; if 0.5%<S≤1.5%, record it as "moderate purple spots"; if 1.5%<S, record it as "severe purple spots". It can be understood that the meaning of the above "both ends" is the part with 2 winding layers formed after winding the head or tail of the negative electrode sheet in a lithium-ion battery with a winding structure. It should be noted that the lithium-ion batteries in the embodiments and comparative examples of this application are taken as an example of the winding structure, but this application is not limited thereto.
[0135] Measurement of energy density:
[0136] First, measure the size of the lithium-ion battery to obtain the thickness T, width W, and length L, and calculate the volume V through the following formula: V = T×W×L.
[0137] Then, charge the lithium-ion battery according to the following operation process and then discharge it to obtain the discharge capacity E of the lithium-ion battery:
[0138] Charging: Charge at a constant current of 1C to 4.45V, and then charge at a constant voltage of 4.45V to 0.025C;
[0139] Discharging: Discharge at a constant current of 0.2C to 3.0V to obtain the discharge energy E.
[0140] The volume energy density (VED) of the lithium-ion battery can be calculated through the following formula: VED (Wh / L) = E / V.
[0141] Example 1-1
[0142] <Preparation of negative electrode sheet>
[0143] The first active material lithium titanate, the anode binder polyacrylic acid, the anode conductive agent conductive carbon black (Super P), and the dispersant carboxymethyl cellulose are mixed evenly according to the mass ratio of 80.9:5.4:0.3:13.4, and then deionized water is added and stirred evenly to prepare a slurry of the first material layer with a solid content of 38 wt%.
[0144] The carbon material artificial graphite, the second active material silicon-carbon material (Dv50 = 8.6 μm), the anode binder polyacrylic acid, the anode conductive agent single-walled carbon nanotubes, and the dispersant carboxymethyl cellulose are mixed evenly according to the mass ratio of 77.3:19.4:2.8:0.3:0.2, and then deionized water is added and stirred evenly to prepare a slurry of the second material layer with a solid content of 40 wt%.
[0145] The slurry of the first material layer is evenly coated on the anode current collector copper foil (copper current collector), and dried at 85 °C to form the first material layer; the slurry of the second material layer is evenly coated on the surface of the first material layer away from the copper foil, and dried at 85 °C to form the second material layer; thus, a semi-finished anode electrode with a single-sided coated anode active material layer is obtained; the above steps are repeated on the other surface of the copper foil to obtain an anode electrode with a double-sided coated anode active material layer. Then, it is cold-pressed and slit to obtain an anode electrode with a specification of 76 mm × 856 mm for use.
[0146] Among them, based on the mass of the anode active material layer, the mass percentage content W1 of the first active material is 7.0%, and the mass percentage content W2 of silicon element is 20%. The particle size Dv50 of the first active material is 1.3 μm, the particle size Dv90 is 0.8 μm, and the specific surface area of the first active material is 5.6 m 2 / g. The single-layer thickness T2 of the first material layer is 5 μm, the single-layer thickness of the second material layer is 95 μm, and the total thickness T1 of the anode active material layer is 100 μm.
[0147] <Preparation of the positive electrode plate>
[0148] The positive electrode active material lithium cobaltate, the positive electrode conductive agent conductive carbon black, and the positive electrode binder polyvinylidene fluoride (PVDF, weight-average molecular weight of 5×10 5 ) are mixed according to the mass ratio of 97.8:1.4:0.8, and N-methylpyrrolidone (NMP) is added as a solvent, and stirred in a vacuum mixer until a positive electrode slurry with a solid content of 75 wt% and a uniform system is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 6 μm, and dried at 90 °C to obtain a positive electrode plate with a single-sided coated positive electrode active material layer (thickness 80 μm). Then, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode plate with a double-sided coated positive electrode active material layer. Then, it is cold-pressed and slit to obtain a positive electrode plate with a specification of 74 mm × 851 mm for use.
[0149] <Preparation of Separator>
[0150] A polyethylene (PE) porous film with a thickness of 8 μm is used as the separator.
[0151] <Preparation of Electrolyte>
[0152] In a dry argon atmosphere, organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed in a mass ratio of 30:50:20 to obtain a basic electrolyte. Then, lithium salt lithium hexafluorophosphate is added to the basic electrolyte and dissolved and mixed evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.
[0153] <Preparation of Lithium-Ion Battery>
[0154] The separator, positive electrode plate, separator, and negative electrode plate prepared above are stacked in sequence and wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film outer package, dried, and then injected with the electrolyte. After vacuum packaging, standing, forming, degassing, trimming, and other processes, a lithium-ion battery is obtained.
[0155] Examples 1-2 to Examples 1-4
[0156] Except for adjusting the relevant preparation parameters according to Table 1, the rest are the same as Example 1-1.
[0157] Among them, when the single-layer thickness T2 of the first material layer changes, the single-layer thickness of the second material layer is adjusted to keep the total thickness of the negative electrode active material layer unchanged; when the single-layer thickness T2 of the first material layer remains unchanged, the single-layer thickness of the second material layer is adjusted to change the total thickness T1 of the negative electrode active material layer.
[0158] Examples 1-5 to Examples 1-10
[0159] Except for adjusting the relevant preparation parameters according to Table 1, the rest are the same as Example 1-1.
[0160] Among them, the mass percentage content of silicon element W2 in the negative electrode active material layer is adjusted by regulating the mass percentage content of artificial graphite and silicon-carbon material in the second material layer. When the mass percentage content of artificial graphite and silicon-carbon material in the second material layer changes, the sum of the mass percentage content of artificial graphite and silicon-carbon material remains unchanged, and the mass percentage content of other components in the second material layer remains unchanged.
[0161] Examples 1-11 to Examples 1-13
[0162] Except for adjusting the relevant preparation parameters according to Table 1, the rest are the same as Example 1-1.
[0163] The carbon nanotubes in Example 1-12 are single-walled carbon nanotubes.
[0164] Examples 2-1 to 2-29
[0165] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-2.
[0166] Example 3-1
[0167] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 1-2.
[0168] Among them, by regulating the mass percentage contents of the carbon material artificial graphite and the second active material in the second material layer, the mass percentage content W2 of silicon element in the negative electrode active material layer remains unchanged. When the mass percentage contents of the carbon material and the second active material in the second material layer change, the sum of the mass percentage contents of the carbon material and the second active material remains unchanged, and the mass percentage contents of other components in the second material layer remain unchanged.
[0169] Example 3-2
[0170] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 1-2.
[0171] Comparative Examples 1 to 6
[0172] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-2.
[0173] Among them, when the single-layer thickness T2 of the first material layer changes, the single-layer thickness of the second material layer is regulated to keep the total thickness of the negative electrode active material layer unchanged; when the single-layer thickness T2 of the first material layer remains unchanged, the single-layer thickness of the second material layer is regulated to change the total thickness T1 of the negative electrode active material layer.
[0174] Comparative Example 7
[0175] Except for using carbon nanotubes with a length of 0.03 μm as the first active material, the rest is the same as Example 1-2.
[0176] Comparative Example 8
[0177] Except for preparing the negative electrode plate according to the following steps, the rest is the same as Example 1-2.
[0178] <Preparation of Negative Electrode Plate>
[0179] Mix artificial graphite and silicon-carbon material (Dv50 = 8.6 μm), negative electrode binder polyacrylic acid, negative electrode conductive agent single-walled carbon nanotubes, and dispersant carboxymethyl cellulose evenly by mass ratio of 56.7:40:2.8:0.3:0.2, and then add deionized water and stir evenly to make a negative electrode slurry with a solid content of 40 wt%.
[0180] The negative electrode paste was evenly coated on the negative electrode current collector copper foil, and after drying at 85 °C, a negative electrode active material layer was formed; the above steps were repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coated negative electrode active material layer. Then, it was cold-pressed and slit to obtain a negative electrode sheet with a specification of 76 mm × 856 mm for use. Among them, the total thickness of the negative electrode active material layer was 100 μm.
[0181] The preparation parameters and performance data of each example and comparative example are shown in Tables 1 to 5.
[0182] Table 1
[0183]
[0184]
[0185] Note: The "\ " in Table 1 indicates no corresponding parameter.
[0186] Table 2
[0187]
[0188]
[0189] Note: The "\ " in Table 2 indicates no corresponding parameter.
[0190] It can be seen from Examples 1-1 to 1-4, Examples 1-11 to 1-13, and Comparative Examples 1 to 8 that in this application, a first material layer containing a first active material is provided between the negative electrode current collector and the second material layer containing a silicon-based material, and the volume change rate of the first active material, the single-layer thickness T2 of the first material layer, and the ratio of the single-layer thickness T2 of the first material layer to the total thickness T1 of the negative electrode active material layer are regulated within the scope of this application, so that the negative electrode current collector has a smaller XY elongation rate at the head, middle, and tail, the purple spot situation at the head and tail of the negative electrode sheet is relatively mild, the negative electrode sheet has a resistivity within the scope of this application, and the secondary battery has a higher energy density. On the basis of alleviating the purple spot phenomenon at the head and tail of the negative electrode sheet of this application, the secondary battery has a higher energy density, indicating that the secondary battery can balance good kinetic performance and a higher energy density. For the secondary batteries of the comparative examples, the first material layer is not provided or the first material layer does not contain the first active material, or at least one of the volume change rate of the first active material, the single-layer thickness T2 of the first material layer, and the ratio of the single-layer thickness T2 of the first material layer to the total thickness T1 of the negative electrode active material layer is not within the scope of this application. The negative electrode current collector has a larger XY elongation rate at the head, middle, and tail, the negative electrode sheet has a more serious purple spot phenomenon at the head and tail, or the secondary battery has a lower energy density, indicating that the secondary batteries of the comparative examples cannot balance kinetic performance and energy density.
[0191] The single-layer thickness T2 of the first material layer and the ratio of the single-layer thickness T2 of the first material layer to the total thickness T1 of the negative electrode active material layer usually affect the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-1 to 1-4 that for the secondary battery with the single-layer thickness T2 of the first material layer and the ratio of the single-layer thickness T2 of the first material layer to the total thickness T1 of the negative electrode active material layer within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole piece are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density.
[0192] The volume change rate of the first active material usually affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-1, 1-11 to 1-13 that for the secondary battery with the volume change rate of the first active material within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole piece are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density. Moreover, the first active material has a lithium intercalation potential, powder conductivity, and lithium ion diffusion coefficient within the scope of this application, has a relatively high initial Coulomb efficiency, the first material layer and the negative electrode current collector have a high adhesion force N1, and the first material layer and the second material layer have a high peel force N2.
[0193] The mass percentage content W1 of the first active material usually affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-1 to 1-4 that for the secondary battery with the mass percentage content W1 of the first active material within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole piece are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density.
[0194] The value of the ratio W2 / W1 of the mass percentage content W2 of silicon element in the negative electrode active material layer to the mass percentage content W1 of the first active material usually affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-1 to 1-10 that for the secondary battery with the value of the ratio W2 / W1 of the mass percentage content W2 of silicon element in the negative electrode active material layer to the mass percentage content W1 of the first active material within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole piece are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density.
[0195] Table 3
[0196]
[0197]
[0198] Note: The "\ " in Table 3 indicates no corresponding parameter.
[0199] Table 4
[0200]
[0201]
[0202] The particle sizes Dv90 and Dv50 of lithium titanate usually affect the kinetic performance and energy density of secondary batteries. It can be seen from Examples 1-2, Examples 2-1 to Examples 2-12 that for secondary batteries using lithium titanate with Dv90 and Dv50 within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole are relatively mild, and the secondary batteries have a high energy density, indicating that the secondary batteries can balance good kinetic performance and high energy density. Moreover, lithium titanate with Dv90 and Dv50 within the scope of this application also has an intercalation lithium potential, powder conductivity, and lithium ion diffusion coefficient within the scope of this application, has a relatively high first Coulomb efficiency, and there is a high adhesion force N1 between the first material layer using lithium titanate with Dv90 and Dv50 within the scope of this application and the negative electrode current collector, and there is a high peeling force N2 between the first material layer and the second material layer.
[0203] The particle sizes Dv90 and Dv50 of titanium dioxide usually affect the kinetic performance and energy density of secondary batteries. It can be seen from Examples 1-10, Examples 2-13 to Examples 2-20 that for secondary batteries using titanium dioxide with Dv90 and Dv50 within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole are relatively mild, and the secondary batteries have a high energy density, indicating that the secondary batteries can balance good kinetic performance and high energy density. Moreover, titanium dioxide with Dv90 and Dv50 within the scope of this application also has an intercalation lithium potential, powder conductivity, and lithium ion diffusion coefficient within the scope of this application, has a relatively high first Coulomb efficiency, and there is a high adhesion force N1 between the first material layer using titanium dioxide with Dv90 and Dv50 within the scope of this application and the negative electrode current collector, and there is a high peeling force N2 between the first material layer and the second material layer.
[0204] The length of the carbon nanotubes generally affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-11, Examples 2-21 to Examples 2-25 that for the secondary battery using carbon nanotubes with lengths within the scope of this application, the XY elongation rates of the head, middle and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density. Moreover, the carbon nanotubes with lengths within the scope of this application also have a lithium intercalation potential, powder conductivity and lithium ion diffusion coefficient within the scope of this application, and have a relatively high first Coulomb efficiency. There is a high adhesion force N1 between the first material layer using carbon nanotubes with lengths within the scope of this application and the negative electrode current collector, and a high peeling force N2 between the first material layer and the second material layer.
[0205] The sheet diameter of graphene generally affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-12, Examples 2-26 to Examples 2-29 that for the secondary battery using graphene with sheet diameters within the scope of this application, the XY elongation rates of the head, middle and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density. Moreover, the graphene with sheet diameters within the scope of this application also has a lithium intercalation potential, powder conductivity and lithium ion diffusion coefficient within the scope of this application, and has a relatively high first Coulomb efficiency. There is a high adhesion force N1 between the first material layer using graphene with sheet diameters within the scope of this application and the negative electrode current collector, and a high peeling force N2 between the first material layer and the second material layer.
[0206] Table 5
[0207]
[0208] The type of the second active material generally affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-2 and Examples 3-1 that for the secondary battery using the type of the second active material within the scope of this application, the XY elongation rates of the head, middle and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode pole are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density.
[0209] The type of the negative electrode current collector usually affects the kinetic performance and energy density of the secondary battery. It can be seen from Examples 1-2 and 3-2 that for the secondary battery using the type of the second active material within the scope of this application, the XY elongation rates of the head, middle, and tail of the negative electrode current collector are small, the purple spot conditions at the head and tail of the negative electrode tab are relatively mild, and the secondary battery has a high energy density, indicating that the secondary battery can balance good kinetic performance and high energy density.
[0210] It should be noted that in this text, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article or device.
[0211] Each embodiment in this specification is described in a related manner. For the same or similar parts among the embodiments, reference can be made to each other, and the differences between each embodiment and other embodiments are emphasized.
[0212] The above are only the preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of this application shall be included within the scope of protection of this application.
Claims
1. A negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a first material layer and a second material layer, and the first material layer is disposed between the negative electrode current collector and the second material layer; the total thickness of the negative electrode active material layer is T1 μm, the thickness of the first material layer is T2 μm, 5 ≤ T2 ≤ 8, 4.6% ≤ T2 / T1×100% ≤ 8.0%; The first material layer includes a first active material, and the volume change rate of the first active material ≤ 10%, where the volume change rate is the volume change rate of the first active material before and after lithium intercalation; The second material layer includes a second active material, and the second active material includes silicon element.
2. The negative electrode tab according to claim 1, wherein Based on the mass of the negative electrode active material layer, the mass percentage content of the first active material is W1, 6.5% ≤ W1 ≤ 8.5%.
3. The negative electrode sheet according to claim 2, wherein, Based on the mass of the negative electrode active material layer, the mass percentage content of the silicon element is W2, 0.4 ≤ W2 / W1 ≤ 4.
6.
4. The negative electrode sheet according to claim 3, wherein, 1.4 ≤ W2 / W1 ≤ 3.
6.
5. The negative electrode sheet according to any one of claims 1 to 3, wherein The type of the first active material includes at least one of lithium titanate, titanium dioxide, carbon nanotubes or graphene; The type of the second active material includes at least one of silicon carbide compound, silicon oxide compound or pure silicon.
6. The negative electrode sheet according to claim 5, wherein, The particle sizes of the lithium titanate and the titanium dioxide independently satisfy: 1.1 μm ≤ Dv90 ≤ 1.5 μm, 0.7 μm ≤ Dv50 ≤ 1.0 μm; The length of the carbon nanotubes is from 0.1 μm to 1.0 μm; The sheet diameter of the graphene is from 0.5 μm to 1.0 μm.
7. The negative electrode sheet according to any one of claims 1 to 3, wherein, The lithium intercalation potential of the first active material is U, 0.13V ≤ U ≤ 1.60V.
8. The negative electrode sheet according to claim 5, wherein, The first active material satisfies at least one of the following characteristics: (1) The specific surface area of the lithium titanate and the titanium dioxide are each independently B1, 3.1 m 2 / g ≤ B1 ≤ 8.2 m 2 / g; The specific surface area of the graphene and the carbon nanotubes are each independently B2, 15 m 2 / g ≤ B2 ≤ 220 m 2 / g; (2) The powder conductivity of the lithium titanate is α1, 2×10 -6 S / m ≤ α1 ≤ 1×10 -4 S / m; the powder conductivity of the titanium dioxide is α2, 3×10 -14 S / m ≤ α2 ≤ 3×10 -10 S / m; the powder conductivity of the graphene is α3, 3×10 6 S / m ≤ α3 ≤ 1×10 8 S / m; the powder conductivity of the carbon nanotubes is α4, 3×10 6 S / m ≤ α4 ≤ 1×10 8 S / m; (3) The powder lithium ion diffusion coefficient of the lithium titanate and the titanium dioxide is δ1, 1.25×10 -9 cm 2 / s ≤ δ1 ≤ 3×10 -7 cm 2 / s; The powder lithium ion diffusion coefficient of the graphene and the carbon nanotubes is δ2, 1×10 -7 cm 2 / s ≤ δ2 ≤ 1×10 -4 cm 2 / s; (4) The first Coulombic efficiency of the first active material is E, 60% < E ≤ 85%.
9. The negative electrode sheet according to any one of claims 1 to 3, wherein, The adhesion force between the first material layer and the negative electrode current collector is N1, 26.5N / m ≤ N1 ≤ 55N / m.
10. The negative electrode sheet according to any one of claims 1 to 3, wherein, The negative electrode current collector includes any one of a copper current collector, a foam copper current collector, a nickel current collector or a stainless steel current collector.
11. The negative electrode sheet according to any one of claims 1 to 3, wherein, The peeling force between the first material layer and the second material layer is N2, 16.7N / m ≤ N2 ≤ 46.2N / m.
12. The negative electrode sheet according to any one of claims 1 to 3, wherein, The resistivity of the negative electrode plate in the thickness direction is Z, 3.7Ω·cm ≤ Z ≤ 15.2Ω·cm.
13. A secondary battery, wherein, The secondary battery includes the negative electrode plate according to any one of claims 1 to 12.
14. An electronic device, wherein, The electronic device includes the secondary battery according to claim 13.